Supermarket Inventory System / Gan Jit Sin - Gan , Jit Sin (2003)
Supermarket Inventory System (SIS) is a client server system with the objective to computerize and enhance the inventory control system for the supermarket. The inventory control system has four users; they are cashiers, supervisors, clerks and managers. The cashiers will use this system to do the daily transaction. The supervisors can check the current status of the stocks by using the system. The clerks can do the usual clerical job by using this system such as insert, delete, view, check, update and maintain the inventory. The managers can check the daily and monthly sales or profit reports, latest in and out stock record, create new user and news by using this system The inventory control system for the supermarket is developed using ASP.NET and SQL 2000 to design and manage the database. The inventory control system for the supermarket is developed with the purpose to enhance the effectiveness and efficiency of the existing manual inventory control system. It enables the company to achieve goals and objectives successfully with minimum resources and effort.